Ukraine & China: opportunities for development are inexhaustible and the interest is mutual - Andriy Kudryachenko; Yevhen Prypik (Cхід, 2020)
The article examines the current socio-economic situation in China, analyzes the process of economic development of the country in the context of historical and political processes of the past, including those that took place in the country during the second half of XX century and the first decades of the current century. The reasons for the success of economic reforms in China, which led to the social modernization of the country and turned it into a powerful economic state, are revealed in the article. Since China’s accession to the WTO in 2001, the leadership of China, realizing the benefits of free trade and openness policy, is actively offering the world new ideas and projects that should contribute to the harmonization of international economic relations and sustainable global development, strengthening China’s positions in the world. The idea of “One Belt, One Road”, proposed by the President of People’s Republic of China Xi Jinping in 2010, was positively received by the world community. Developing this concept, in 2013 the Chinese leader proposed the new projects to implement the idea of “One Belt, One Road”. In particular, these were two large-scale projects: the “Silk Road Economic Belt” and “XXI century Maritime Silk Road”. The projects are aimed at building the new trans-Eurasian economic corridors and new sea routes, which should expand China’s ability to interact with other countries and strengthen its presence around the world. Considerable attention in the article has also been paid to the analysis of the results and prospects of Ukrainian-Chinese cooperation over the last decades since the establishment of diplomatic relations, which have been transformed into a strategic partnership. The paper presents the importance and role of the active involvement of Ukraine in such a global project as the concept of “One Belt, One Road”, which would allow the realization of the geopolitical, scientific, technical, intellectual and economic potential of Ukraine on a fuller scale. The deepening of cooperation between Ukraine and China would lead two sides on the path of sustainable, long-term development and would contribute to the prosperity of the two countries.